The Global Scapes of Postmodernity: A Proposed Model for "Global Cultural Flow" in Fashion Education - Richardson, Tina (Fashion theory, 2021)
This article proposes the use of Arjun Appadurai's global scapes model, highlighted in 'Disjuncture and Difference in the Global Cultural Economy', as a tool for teaching fashion theory. Originally designed as a one-off lecture on globalization for undergraduates on a 'Fashion and Society' module, it has now been extended to cover the whole of the teaching on this module for a semester, with all subsequent classes referring back to Appadurai's theory of scapes. Globalization is a hugely complex subject area, which is very important for students of fashion today. The reworking of this model to fit the worldwide network that makes up the fashion industry helps students to see their own place, and that of others, on a global scale. It also opens up discussion on important subjects that are all connected to fashion, such as ethics, geo-politics, discourse and practice.